Stochastic trends and cointegration in the market for equities - Lucy F. Ackert; Marie D. Racine (Federal Reserve Bank of Atlanta, 1998)
We use a no-arbitrage, cost-of-carry pricing model to examine whether equity spot and futures markets are cointegrated. A stock index and its futures price should be cointegrated if the cost of carry is stationary. Otherwise, the appropriate cointegrating relationship is trivariate and includes the index, futures price, and cost of carry. We study the relationships among the Standard and Poor's 500 index, associated index futures price series, and interest rate for January 4, 1988, through June 30, 1995, and find that all three series are nonstationary. We further find that the index and futures price are not cointegrated unless the cost of carry is included in the cointegrating relationship. Our findings are consistent with the no-arbitrage pricing model and do not appear to be sensitive to the presence of structural breaks in the series.
Keywords: 330; Cointegration; Financial markets